Productivity Growth in U.S. Agriculture: 1948-2013 - V. Eldon Ball; Richard Nehring; Sun Ling Wang (International Productivity Monitor, 2016)
It is widely reported that productivity growth is the main contributor to output growth in U.S. agriculture. This article provides estimates of output growth over the postwar period and decomposes that growth into the contributions of input growth and productivity growth. The analysis is based on recently revised production accounts for agriculture. Our findings are fully consistent with those reported in the literature. Productivity growth dominates input growth as a source of output growth in the sector.